Pengaruh Budaya Kerja dan Kepuasan KerjaTerhadap Kinerja Karyawan (Studi Kasus pada PT. Vinsen Global Indonesia Subang) - Herlina, Herlina; Kartini, Tri; Firdaus, Keisha Azzalia; Mulyeni, Sri (PDPI, 2024)
This study aims to determine the effect work culture and job satisfaction on employee performance. This study was conducted at PT Vinsen Global Indonesia. The population is 64 employees of PT Vinsen Global Indonesia in Subang, without using a sample. Data collected directly from respondents with a questionnaire. This is explanatory research. The data analysis technique used is the Pearson Bivariate Correlation. The results prove that work culture has a significant effect on employee performance (H1), job satisfaction has a significant effect on employee performance (H2), and work culture has a significant effect on job satisfaction (H3). Based on these results can it can be interpreted that work culture and employee job satisfaction are important components in order to improve the performance of employees of PT Vinsen Global Indonesia. With a good work culture implemented and employees getting job satisfaction, this is a source of organizational competitive advantage to deal with rapidly changing business environment.